The Effect of Strategic Management Practice on Organizational Performance: The Case of Ethio Telecom - Leykun Arega; Yohannes Workeaferahu Elifneh (International Journal of Engineering and Management Research, 2024)
The aim of this research paper was to examine the effect of strategic management practices on organization performance in the case of Ethio telecom (the leading telecom company in Ethiopia). To conduct this study, the study used an explanatory research design to examine the effect of strategic management practice (strategy formulation, strategy implementation and strategy evaluation) on organization performance. The target population comprised 517 Ethio telecom employees and 226 samples drawn. The study used questionnaires for data collection. Accordingly, 226 questionnaires were distributed through a google form link and 206 questionnaires were properly filled. Both descriptive and inferential analysis techniques have been used to analyze the data using SPSS version 23 tool. The results of the study showed that from the dimensions of strategic management practices, strategic evaluation is the most important predictor of organization performance and followed by strategic formulation; while strategic implementation is moderately related in terms of magnitude of the effect.